Effect of cutting parameters on surface roughness in turning of annealed AISI-1020 steel (2018)
This study focuses on the effects of cutting parameters such as cutting speed (Vc), feed rate (f), and depth of cut (d) on roughness induced on the surface of annealed AISI 1020 steel when machined by turning using carbide insert tools. The results indicated that surface roughness increased when feed rate increased and cutting speed decreased. Depth of cut slightly influenced roughness. Analysis of variance and multiple regression techniques were used to formulate a quantitative equation for estimating predicted values of roughness as functions of the cutting parameters. The results showed that cutting speed is the most influencing parameter on surface roughness (69.35%), followed by feed rate (30.13%), while depth of cut failed to affect the responses substantially (0.52%). The proposed model can be used to select the optimum parameters for minimum surface roughness in metal turning.